A Study of Nutritional Status of Adolescent Girls in Rural Area of Bhopal District - Joshi, Sheloj M; Likhar, Swarna; Agarwal, Sanjay S; Mishra, Mahesh Kumar; Shukla, Umashankar (National Journal of Community Medicine, 2014)
Introduction: Adolescent girls are backbone of healthy and progressive family and thus future builders of positive health of community. To attain healthy reproductive outcome and efficient physical activity nutritional status of adolescent girl is valuable. In India especially in rural area there is high prevalence of malnutrition amongst adolescent girls. Objectives: The objective of the study was to determine the nutritional status of adolescent girls in rural area of Bhopal district and to study the socio-demographic factors affecting the nutritional status of adolescent girls in rural area of Bhopal district. Material & method: A community based cross sectional study was carried out amongst adolescent girls in the age group of 10-19 years. Two Government schools of Ratua village of Bhopal district were selected for study purpose. Study period was from June to August2013.Total 200 adolescent girls were included. Variables included were age, socio-economical status, weight, Height and dietary intake pattern. Statistical analysis: Data was analysed using SPSS version 20 statistical software and Odds ratio and Chi square test was applied to test the strength of association between the variables. Result: Amongst all adolescent girls 69% suffered from under nutrition. Only 31% girls had normal nutritional status. Majority i.e. 87.20% of adolescent girls belonging to the age group of 10-14 years were undernourished Conclusion: Majority of rural adolescent girls were under nourished. There was significant association between socio-economic status (SES) and nutritional status of adolescent girls. Nutritional status has profound effect on health and school performance of adolescent girls.